Consumers' Intention to Stay in Green Hotels in Australia: Theorization and Implications. (January 2020) - Nimri, Rawan; Patiar, Anoop; Kensbock, Sandra; Jin, Xin
Despite multiple calls to protect the environment, adopting environmentally friendly behaviors is still considered to be one of the most persistent challenges in behavior transformation agendas. This study sought to expand existing knowledge of hotel consumers' green behaviors by developing and testing an extended model of the theory of planned behavior. More specifically, this study incorporated past experience into the theory of planned behavior model to understand comprehensively consumers' decision-making processes with respect to their intentions to stay at a green hotel. Results from the structural model from a sample of 781 Australian travelers showed that the proposed theoretical framework had a strong ability to predict intention and identified the prominent role of past experience in generating intention. The results offer further perspectives into consumers' decision-making processes, which can assist hotel managers in the development and execution of hotel operations accounting for consumers' environmentally friendly purchase behavior.